Improved tolerance of apple plants to drought stress and nitrogen utilization by modulating the rhizosphere microbiome via melatonin and dopamine - Du, Peihua; Cao, Yang; Yin, Baoying; Zhou, Shasha; Li, Zhongyong; Zhang, Xueying; Xu, Jizhong; Liang, Bowen (Frontiers in Microbiology, 2022)
This study explored the contributions of melatonin and dopamine to the uptake and utilization of nitrogen and the formation of rhizosphere microbial communities in ‘Tianhong 2’/M. hupehensis, with the goal improving plant resistance to drought stress. Drought stress was artificially induced, and melatonin or dopamine was regularly applied to the soil. After 60 days of treatment, plant indices were determined and the structure of the rhizosphere microbial community was evaluated using high-throughput sequencing technology. The findings revealed two ways through which melatonin and dopamine alleviate the inhibition of growth and development caused by drought stress by promoting nitrogen uptake and utilization in plants. First, melatonin and dopamine promote the absorption and utilization of nitrogen under drought stress by directly activating nitrogen transporters and nitrogen metabolism-related enzymes in the plant. Second, they promote the absorption of nitrogen by regulating the abundances of specific microbial populations, thereby accelerating the transformation of the soil nitrogen pool to available nitrogen that can be absorbed directly by plant roots and utilized by plants. These findings provide a new framework for understanding how melatonin and dopamine regulate the uptake and utilization of nitrogen in plants and improve their ability to cope with environmental disturbances.